Controversies in the Local Management of Lung Cancer - John M. Varlotto; Giulia Veronesi (Frontiers Media SA, 2018)
This special edition of Frontiers in Oncology reviews the current efficacy and limitations of surgical and radiotherapeutic management of lung cancer and provides insight into how local management options may change in the future.
English
Keywords: radiation techniques; neo-adjuvant treatment; heavy ion therapy; small cell lung cancer; surgery